2019
DOI: 10.1111/psyp.13351
|View full text |Cite
|
Sign up to set email alerts
|

The P3b and P600(s): Positive contributions to language comprehension

Abstract: Since its discovery in the 1960s, the P300 has been contributing both directly and indirectly to language research. Perhaps most notably, it has been suggested that the P600, an ERP component that was first characterized in the context of syntactic processing, could be a variant of the P3b subcomponent of the P300. Here, we review studies on both sides of the debate. We also review the “semantic P600,” a positivity with a similar time course and distribution to the P600 seen for syntactic manipulations but tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 98 publications
(150 reference statements)
10
87
0
Order By: Relevance
“…The Wenzel study, notably, also established an ERP in addition to the N400, a left-lateralized late positivity for unrelated stimuli. This matches the LPC or P600 responses that are sometimes reported to co-occur with N400 tasks, and that have been interpreted as late P300's by some [53]. However, this response is in the opposite direction as ERP in the Geuze et al (2014) study, where the unrelated stimuli were more negative.…”
Section: Inferring Information About the User's Active Mental Contextsupporting
confidence: 84%
“…The Wenzel study, notably, also established an ERP in addition to the N400, a left-lateralized late positivity for unrelated stimuli. This matches the LPC or P600 responses that are sometimes reported to co-occur with N400 tasks, and that have been interpreted as late P300's by some [53]. However, this response is in the opposite direction as ERP in the Geuze et al (2014) study, where the unrelated stimuli were more negative.…”
Section: Inferring Information About the User's Active Mental Contextsupporting
confidence: 84%
“…Categorization success modulates a P3(00)-like ERP, specifically, an occipitoparietal P600 between 500 and 700 ms, which seems related to internally evaluating the success of earlier (e.g., N3) decision processes in state 2 (Schendan & Kutas, 2002;Schendan & Maher, 2009) and potentially higher-order semantic processing beyond the N400 . The P600 is more positive for better memory matches, more confident and successful categorization, and canonical than unusual views on categorization (Schendan & Kutas, 2003), and a semantic P600 has been reported for semantic anomalies in language research (Leckey & Federmeier, 2019), suggesting a semantic evaluation role (van Herten, Kolk, & Chwilla, 2005) perhaps related to the name of the object with picture stimuli.…”
Section: State M: Details and Further Evidencementioning
confidence: 89%
“…For example, violations of thematic‐role assignment (e.g., the eggs would eat ) do not modulate the N400 but instead produce a late positive potential with a similar timing and topography to the P600 effect that is commonly observed to morphosyntactic violations (Kuperberg, Sitnikova, Caplan, & Holcomb, ); this effect has been termed the semantic P600. Similarly, many studies have reported biphasic ERP responses to semantic congruity violations, such that large N400 amplitudes to semantically anomalous words are often immediately followed by a posterior LPC, with a similar morphology and distribution to the (semantic) P600 (Leckey & Federmeier, ; Van Petten & Luka, ). Indeed, Brouwer and colleagues () have recently proposed a neurocomputational model accounting for the biphasic N400/LPC complex in terms of a single‐stream “retrieval‐integration” cycle, in which the N400 reflects semantic memory retrieval and the LPC reflects a process where the activated memory representation is integrated into an updated message‐level representation.…”
Section: Introductionmentioning
confidence: 88%